Effect of fire in weeds of agroforestry system, Pará, Brazil - Alvino-Rayol, Fabrízia de Oliveira; Rayol, Breno Pinto (Revista de Ciências Agroveterinárias, 2020)
The objective of this study was to assess the effect of fire on the structure, floristic composition, and diversity of weeds in an agroforestry system with two types of preparation of the area: with and without burning. The agroforestry system was composed of the species: Schizolobium amazonicum, Euterpe oleracea, and Theobroma grandiflorum. For the sampling of the vegetation of the weeds, a wooden template of 0.25 m2 was used, randomly launched 20 times in each area assessed. The diversity of species (Shannon Diversity Index) and vegetation cover rate were calculated. The inventoried species were collected and sent for identification in the herbariums of the region. The diversity of species did not differ statistically in the two treatments. However, the highest rate of spontaneous vegetation cover was observed in the area prepared with the use of fire. The floristic composition of the spontaneous vegetation presented only 32.3% of similarity between the two areas. The species that showed major importance in the emergent flora in both areas was Myrciaria tenella. Fire influenced the floristic composition and vegetation cover rate in the assessed areas.